Inequality and growth: A joint analysis of demand and supply - Ling Shen (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
The paper contributes to the literature of income inequality and economic growth in two directions. First, it analyzes the impact of income inequality on economic growth both through the supply of human capital and the incentive to invent induced by the demand for better quality goods. Secondly, I decompose Gini-coefficient in two variables, which have different effect on the economic performance. Thus, our result suggests that the empirical research on the base of Gini-coefficient can not generate an overall relationship between income inequality and economic growth.
Keywords: 330